Representasi Nilai-nilai Budaya Masyarakat Suku Nias dalam Novel Manusia Langit Karya J.A. Sonjaya: Kajian Antropologi Sastra - Herman Didipu (HISKI, 2017)
This study aims to describe the various cultural values of the people of Nias tribe that is represented in the ethnographic novel of Manusia Langit by J.A. Sonjaya. The approach used is the approach of literary anthropology, an interdisciplinary approach that specifically examines various aspects of human culture which is reflected through literary works. The method used in this research is descriptive qualitative method. To analyze the data, used content analysis techniques that include the stages of data identification, data classification, data interpretation, and data interpretation. Based on the research results, found six cultural values of the people of Nias tribe that is represented in the novel of Manusia Langit. First, uphold the dignity of women. Second, respect for high status people. Third, upholding dignity and prestige. Fourth, deliberation and consensus. Fifth, the values of kinship and brotherhood in custom. Sixth, appreciate guests.